PENGEMBANGAN KREATIVITAS BERPIKIR ANAK USIA DINI DENGAN PERMAINAN BAHASA - Aushofil Karimah (LP2M Universitas Ibrahimy, 2015)
Profesional education say education at an early age will determine the future success and a personality in the future. Therefore it have to care seriously and give an good education to develop Â the knowledge and skills of children at an early age at each stage of his development.